Macroeconomic Determinants of Employment in Nigeria's Services Sector: Do Foreign Direct Investment and Exchange Rate Matter? - Aigheyisi, Oziengbe (Revista de Economia Mackenzie, 2023)
The study employs the ARDL modeling technique to investigate the determinants of employment generation in Nigeria’s services sector, focusing mainly on the roles of foreign direct investment and exchange rate movements during the 1991-2019 period. The study finds that in the short-run, FDI positively affects employment generation in the services sector while currency depreciation adversely affects it with a one-year lag. The long run employment generation effect of the FDI in the services sector remains positive, but loses its statistical significance, while the effect of currency depreciation on services sector employment is positive and significant. It is also found that economic growth positively affects service sector employment generation in the short-and long-run, though the effect is only significant in the short-run. The effect of trade openness is positive and significant in the short-run, but also turns out to be non-significant in the long-run. Financial sector development favours employment generation in the services sector in the short-and long-run. Based on the evidence it is recommended that the government make effort to enhance the attractiveness of various sectors of the economy to FDI and guard against undue appreciation of the nation’s currency. It is also recommended that economic growth and the development of financial system be prioritized. In view of the transience of the effect of trade openness on employment generation in the services sector, caution must be exercised in implementing trade liberalization policies. These measures, if implemented, are expected to enhance job-creation in the nation’s services sector.